Kinerja Bidan dalam Deteksi Dini Penyimpangan Tumbuh Kembang Anak - Sri Utami; Nursalam Nursalam; Rachmat Hargono; Rekawati Susilaningrum (Jurnal Ners, 2016)
Background: Children are the future of a nation.They should be able to grow and develop optimally. One effort that can be done to help children grow and develop optimally is through an early detection of deviationsin child’s growth. The purpose of this study was to develop a model of midwife performance improvement through the optimization of self leadership strategy. Method: This study was an observational study with cross sectional design. The subjects were 222 midwives working at the health center services in the area of Surabaya Health Department taken by using proportional random sampling technique. Exogenous variables were job design, history of training of early detection of deviationsin child’s growth, self leadership strategy, midwife skill, midwife activity in early detection of deviationsin child’s growth, andendogenous variable was midwife performance in early detection of deviationsin child’s growth. Data were analyzed using Partial Least Square (PLS). Result: The result of inner model analysis showed that the value of T-statistic of the influence of self leadership strategyon midwife performance improvement, the influence of midwife skill on activity performance improvement, the influence of self leadership strategyon activity performance improvement and on midwife performance improvement was higher than T-table (1.96). Whereas, training of early detection of deviationsin child’s growth did not influence midwife skill improvement since the value of T-statistic was lower than T-table (<1.96). In addition, there was also no influence of job design on midwife skill improvement and on midwife activity performance improvement in early detection of deviationsin child’s growth. Discussion: Optimization of midwife self-leadership ability is a factor to be considered as an effort to improve the performance of midwives in early detection of deviationsin child’s growth.